El efecto del programa acompañamiento pedagógico sobre los rendimientos de los estudiantes de escuelas públicas rurales del Perú - Rodríguez G., José S. (2016)
The aim of the present study is to evaluate the effect of a teacher training program implemented by the Ministry of Education called Pedagogical Accompaniment on school performance and its main determinants. Using non-experimental impact evaluation techniques, measurements are made exploiting the test results of the Census Student Assessment of 2013. The results provide evidence of positive and statistically significant impacts. However, the size of these impacts is relatively moderate. Several hypotheses could explain the effect size. These are discussed in the paper. On the other hand, having a bachelor's degree instead of a pedagogical degree and multigrade experience favors significantly the positive results of the intervention.